ANALISIS PENGELOLAAN DAN PENYELENGGARAAN PENDIDIKAN BERDASARKAN PP.17 TAHUN 2010 DI INSTITUT AGAMA KRISTEN NEGERI KUPANG - Lopis, Yorhans S; Lao, Hendrik A.E (Jurnal Dedikasi Pendidikan, 2024)
Analysis of the management and administration of education based on PP. 17 of 2010, that the management and administration of education is an inseparable part of the 8 national education standards as a benchmark for the quality of education implementation. The method used in this research is a qualitative method with data collection techniques by interviewing 3 education managers or administrators. The results found are as follows: 1) evaluate the management and implementation of education, there needs to be an increase in the competency of education personnel and education staff in each education unit so that education quality is achieved. 2) implementation of education management and administration requires good collaboration between education units and stakeholders such as parents, non-educational institutions or education practitioners to improve the quality of education management and administration. 3) the relevance of education management that has been carried out based on Law no. 17 of 2010 that the relevance of existing education is running well, but there needs to be equal distribution of educational facilities and infrastructure and funding for education with a touch of educational technology as a means of learning. The conclusion from the analysis is that the evaluation, implementation and relevance of education management and administration are effective and efficient but need to be transparent in management.